Secondary battery and electric device

By using composite positive electrode active materials with doped elements, the problems of low energy density, poor low temperature performance and poor circulation performance of lithium manganese iron phosphate secondary batteries are solved, and higher energy density and better low temperature and circulation performance are achieved.

CN119725676AActive Publication Date: 2025-03-28SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411873317.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate secondary batteries have low energy density, poor low temperature performance and poor circulation performance.

Method used

Two active materials containing doped elements are used as the positive electrode active material. The second active material mainly exists in the form of primary particles, and the first active material mainly exists in the form of secondary spherical morphology. The kinetic properties of the positive electrode active material are optimized by regulating particle size, true density, particle grading, compaction density and content and types of doped elements.

Benefits of technology

It improves the energy density, low temperature performance and cycling performance of secondary batteries, and is suitable for practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725676A_ABST
    Figure CN119725676A_ABST
Patent Text Reader

Abstract

The invention discloses a secondary battery and an electric device. According to the secondary battery disclosed by the invention, the lithium manganese iron phosphate with the secondary sphere morphology and the primary particles containing the doping elements are used as the positive electrode active material, and the average particle size of the lithium manganese iron phosphate with the secondary sphere morphology, the true density and the particle composition of the positive electrode active material, the compaction density of the positive electrode plate and the content and the type of the doping elements are regulated and controlled; the invention aims to reduce gaps among positive electrode active material particles, optimize the dynamic performance of the positive electrode active material, improve the powder compaction density and gram volume exertion of the positive electrode active material, and achieve the purpose of improving the energy density, low-temperature performance and cycle performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to secondary batteries and electrical devices. Background Art

[0002] The positive electrode active material plays a decisive role in the energy density, power, safety, life and other properties of secondary batteries. At present, the positive electrode active materials used in secondary batteries are mainly lithium nickel cobalt manganese oxide, lithium iron phosphate and lithium manganese iron phosphate. Among them, lithium nickel cobalt manganese oxide has a high energy density, but it is very expensive and cannot be reduced in cost; lithium iron phosphate is relatively cheap, highly safe, and has good cycle performance, but its energy density is low, and it is difficult to increase the energy density due to the material itself, which limits its application.

[0003] Lithium iron manganese phosphate has the same theoretical gram capacity as lithium iron phosphate (170mAh / g), and the potential of lithium iron phosphate to lithium can reach up to 4.1V, which is much higher than the 3.4V of lithium iron phosphate. The higher voltage platform makes the secondary battery using lithium iron phosphate as the positive electrode active material have the potential advantage of higher energy density, and the safety performance and cost are close to those of lithium iron phosphate. However, the band gap between the conduction band and the valence band of lithium iron phosphate is relatively wide, and the activation energy formed during the lithium ion conduction process is higher, resulting in the electronic conductivity and ion conductivity of lithium iron phosphate being significantly worse than that of lithium iron phosphate, which in turn leads to the gram capacity of lithium iron phosphate being lower than that of lithium iron phosphate, the power performance is worse than that of lithium iron phosphate, and the low temperature performance is also poor. In addition, due to the presence of Mn in lithium iron phosphate materials, 3+ The Jahn-Teller effect is likely to occur, causing a large lattice volume change, and Mn 3+ Disproportionation reaction and Mn 2+ dissolution, resulting in deterioration of high temperature cycle performance. Summary of the invention

[0004] The purpose of the present application is to overcome the defects of the existing lithium manganese iron phosphate secondary battery, such as low energy density, poor low temperature performance and poor cycle performance, and to provide a secondary battery and an electrical device to improve the energy density, low temperature performance and cycle performance of the lithium manganese iron phosphate secondary battery.

[0005] In order to achieve the above-mentioned purpose, in a first aspect, the present application provides a secondary battery, which includes a positive electrode plate, wherein the positive electrode plate includes a positive electrode active material, wherein the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, and the positive electrode active material contains an M element;

[0006] The M element includes at least one of Mg, Ti, V, Zn, Al, Co, W, Mo, Y, Nb, In, La, Zr, Ce, Sr, and Sb;

[0007] The first positive electrode active material comprises lithium manganese iron phosphate with a secondary spherical morphology, and the lithium manganese iron phosphate with a secondary spherical morphology is formed by aggregation of primary particles;

[0008] The second positive electrode active material comprises primary particles of lithium manganese iron phosphate;

[0009] The positive electrode sheet satisfies the following relationship:

[0010] 1.85≤D1×D2×ρ×PD×(Dv 90 -Dv 10 )÷Dv 50 ÷c≤7.42;

[0011] Wherein, D1 nm is the average particle size of the primary particles in the lithium manganese iron phosphate with secondary spherical morphology;

[0012] D2μm is the average particle size of the lithium manganese iron phosphate with secondary spherical morphology;

[0013] ρg / cm 3 is the true density of the positive electrode active material;

[0014] PD g / cm 3 is the compaction density of the positive electrode sheet;

[0015] Dv 10 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 10%;

[0016] Dv 50 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 50%;

[0017] Dv 90 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 90%;

[0018] c ppm is the content of the M element in the positive electrode active material.

[0019] As an implementation scheme of the present application, the D1 nm satisfies: 50 nm≤D1 nm≤200 nm.

[0020] As an implementation scheme of the present application, the D2μm satisfies: 4.1μm≤D2μm≤9μm.

[0021] As an embodiment of the present application, the Dv 50 μm satisfies: 0.8μm≤Dv 50 μm≤10.5μm.

[0022] As an embodiment of the present application, the Dv90 μm meets: 4.5μm≤Dv 90 μm≤30μm.

[0023] As an embodiment of the present application, the Dv 10 μm satisfies: 0.25μm≤Dv 10 μm≤2.6μm.

[0024] As an embodiment of the present application, the PD g / cm 3 Meets: 2.1g / cm 3 ≤PD g / cm 3 ≤2.55g / cm 3 .

[0025] As an embodiment of the present application, the ρg / cm 3 Meets: 3.4g / cm 3 ≤ρg / cm 3 ≤3.6g / cm 3 .

[0026] As an embodiment of the present application, the c ppm satisfies: 2000ppm≤c ppm≤8000ppm.

[0027] As an embodiment of the present application, the surface density of the positive electrode sheet is 0.125-0.35 g / 1540.25 mm 2 .

[0028] As an embodiment of the present application, the average particle size of the lithium manganese iron phosphate of the primary particles in the second positive electrode active material is 100 to 400 nm.

[0029] In the second aspect of the present application, the present application also provides an electrical device comprising the secondary battery. The electrical device comprises the secondary battery of the present application, which has high energy density, low internal resistance, good low temperature performance and excellent cycle performance, and is more suitable for practical applications.

[0030] The beneficial effects of the present application are as follows: the secondary battery of the present application compounds two active materials containing doping elements as a whole positive electrode active material, wherein the second active material mainly exists in the form of primary particles, and the first active material mainly exists in the form of secondary spherical morphology, and the average particle size of lithium manganese iron phosphate with secondary spherical morphology in the first positive electrode active material, the true density and particle grading of the positive electrode active material, the compaction density of the positive electrode plate, the content and type of doping elements are regulated to reduce the gaps between the positive electrode active material particles and optimize the kinetic properties of the positive electrode active material, improve the powder compaction density and gram capacity of the positive electrode active material, and achieve the purpose of improving the energy density, low temperature performance and cycle performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the surface morphology of the positive electrode.

[0032] Figure 2 This is the cross-sectional morphology of the positive electrode. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0034] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0035] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0036] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0037] The present application is further described below with specific embodiments:

[0038] The present application provides a secondary battery, which includes a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode active material, wherein the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, and the positive electrode active material contains an M element;

[0039] The M element includes at least one of Mg, Ti, V, Zn, Al, Co, W, Mo, Y, Nb, In, La, Zr, Ce, Sr, and Sb;

[0040] The first positive electrode active material comprises lithium manganese iron phosphate with a secondary spherical morphology, and the lithium manganese iron phosphate with a secondary spherical morphology is formed by aggregation of primary particles;

[0041] The second positive electrode active material comprises primary particles of lithium manganese iron phosphate;

[0042] The positive electrode sheet satisfies the following relationship:

[0043] 1.85≤D1×D2×ρ×PD×(Dv 90 -Dv 10 )÷Dv 50 ÷c≤7.42;

[0044] Wherein, D1 nm is the average particle size of the primary particles in the lithium manganese iron phosphate with secondary spherical morphology;

[0045] D2μm is the average particle size of the lithium manganese iron phosphate with secondary spherical morphology;

[0046] ρg / cm 3 is the true density of the positive electrode active material;

[0047] PD g / cm 3 is the compaction density of the positive electrode sheet;

[0048] Dv 10 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 10%;

[0049] Dv 50 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 50%;

[0050] Dv 90 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 90%;

[0051] c ppm is the content of the M element in the positive electrode active material.

[0052] The present application uses lithium manganese iron phosphate with secondary spherical morphology and primary particles containing doped elements as the positive electrode active material, and regulates the average particle size of the lithium manganese iron phosphate with secondary spherical morphology, the true density and particle grading of the positive electrode active material, the compaction density of the positive electrode plate, the content and type of the doping elements, so as to reduce the gaps between the particles of the positive electrode active material and optimize the kinetic properties of the positive electrode active material, improve the powder compaction density and gram capacity of the positive electrode active material, and achieve the purpose of improving the energy density, low temperature performance and cycle performance of the secondary battery.

[0053] In some embodiments, the D1 nm satisfies: 50 nm≤D1 nm≤200 nm. Exemplarily, the D1 nm is a range value of one or any two of 50 nm, 75 nm, 100 nm, 125 nm, 150 nm, 175 nm, and 200 nm.

[0054] In the present application, the positive electrode active material of the secondary battery includes two types of lithium iron manganese phosphate, which are marked as the first positive electrode active material and the second positive electrode active material. The first positive electrode active material mainly exists in a secondary spherical morphology, and the lithium iron manganese phosphate with a secondary spherical morphology is a spherical or quasi-spherical particle formed by the aggregation of primary particles. The second positive electrode active material mainly exists in the form of primary particles, and the primary particles refer to primary particles that have not been agglomerated or artificially spherical. The first positive electrode active material and the second positive electrode active material in the present application each independently contain a doping element M, especially when the M element selects at least one of Mg, Ti, V, Zn, Al, Co, W, Mo, Y, Nb, In, La, Zr, Ce, Sr, and Sb, the structural stability of lithium iron manganese phosphate and the dynamic performance of lithium iron manganese phosphate can be effectively improved, and the lithium iron manganese phosphate of the primary particles and the particles of the secondary spherical morphology are matched with each other, which is conducive to taking into account the gram capacity and compaction density, and improving the energy density, low temperature performance and cycle performance of the secondary battery.

[0055] In some embodiments, M comprises at least one of Ti, Mg, Co, W, V, Nb, and In.

[0056] The present application nanosizes the primary particles of the first positive electrode active material, which is beneficial to shortening the diffusion distance of lithium ions, further improving the charging capacity and kinetic performance of the positive electrode active material, and enhancing the gram capacity of the positive electrode active material, thereby improving the energy density, low temperature performance and cycle performance of the secondary battery.

[0057] In some embodiments, the D2μm satisfies: 4.1μm≤D2μm≤9μm. Exemplarily, the D2μm is a range value of one or any two of 4.1μm, 5μm, 6μm, 7μm, 8μm, and 9μm. By controlling the average particle size of lithium manganese iron phosphate with secondary spherical morphology within the range of 4.1μm to 9μm, the specific surface area of ​​the particles can be reduced, the particle stability can be improved, the processing defects caused by the nano-sizing of the primary particles of the first positive electrode active material can be improved, and the energy density of the secondary battery can be further improved. In addition, the secondary particle size of the first positive electrode active material of the present application is relatively suitable, and can be matched with the second positive electrode active material to achieve large and small particle grading, improve the stacking effect of the particles, and improve the energy density, cycle performance and low temperature performance of the secondary battery.

[0058] In some embodiments, the Dv 50 μm satisfies: 0.8μm≤Dv 50 μm≤10.5μm. 50 μm is a range value of one or any two of 0.8 μm, 1.0 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10.5 μm.

[0059] In some embodiments, the Dv 90 μm meets: 4.5μm≤Dv 90 μm≤30μm. 90 μm is a range value of one or any two of 4.5 μm, 7.5 μm, 10 μm, 12.5 μm, 15 μm, 20 μm, 22.5 μm, 25 μm, 27.5 μm, and 30 μm.

[0060] In some embodiments, the Dv 10 μm satisfies: 0.25μm≤Dv 10 μm≤2.6μm. 10 μm is a range value of one or any two of 0.25 μm, 0.5 μm, 0.75 μm, 1.0 μm, 1.25 μm, 1.5 μm, 1.75 μm, 2.0 μm, 2.25 μm, and 2.6 μm.

[0061] In some embodiments, the PD g / cm 3 Meets: 2.1g / cm 3 ≤PD g / cm 3 ≤2.55g / cm 3 . For example, the PD g / cm 3 2.10g / cm 3 , 2.20g / cm 3 , 2.30g / cm 3 , 2.40g / cm 3 , 2.55g / cm 3 The range value of one or both of them.

[0062] Controlling the Dv of the positive electrode active material 10 、Dv 10 、Dv 90 Within the scope of this application, reasonable particle grading can be achieved, the gaps between the positive electrode active material particles can be reduced, the packing density of the particles can be increased, and the compaction density of the positive electrode sheet can be increased, thereby improving the energy density, low temperature performance and cycle performance of the secondary battery. In addition, it is also beneficial to ensure the processing performance of the positive electrode slurry and the positive electrode sheet, and the capacity and power performance of the secondary battery.

[0063] In some embodiments, the ρg / cm 3 Meets: 3.4g / cm 3 ≤ρg / cm 3 ≤3.6g / cm 3 For example, the ρg / cm 3 3.40g / cm 3、3.45g / cm 3 、3.50g / cm 3 、3.55g / cm 3 、3.60g / cm 3 The present application can control the true density of the positive electrode active material within the above range by controlling the proportion of the first positive electrode active material and the second positive electrode active material, which is beneficial to improving the specific capacity and kinetic performance of the positive electrode active material.

[0064] In some embodiments, the c ppm satisfies: 2000ppm≤c ppm≤8000ppm. Exemplarily, the c ppm is a range value of one or any two of 2000ppm, 3000ppm, 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm. When the application selects the addition amount of the M element within the above concentration range, the lithium ion diffusion coefficient and stability of the positive electrode active material can be effectively improved, the kinetic performance and life of the positive electrode active material can be improved, and the cycle performance of the secondary battery can be improved.

[0065] In some embodiments, the single-sided surface density of the positive electrode sheet is 0.125-0.35 g / 1540.25 mm 2 For example, the single-sided surface density of the positive electrode sheet may be 0.125 g / 1540.25 mm 2 , 0.150g / 1540.25mm 2 , 0.175g / 1540.25mm 2 , 0.200g / 1540.25mm 2 , 0.225g / 1540.25mm 2 , 0.250g / 1540.25mm 2 , 0.275g / 1540.25mm 2 , 0.300g / 1540.25mm 2 , 0.325g / 1540.25mm 2 , 0.350g / 1540.25mm 2 When the single-sided surface density of the positive electrode sheet is maintained within the above range, it is not only beneficial to improve the energy density, low temperature performance and cycle performance, but also can minimize the amount and reduce the cost while ensuring the electrochemical performance of the secondary battery.

[0066] In some embodiments, the average particle size of the lithium manganese iron phosphate of the primary particles in the second positive electrode active material is represented by D3nm, and the average particle size D3nm of the lithium manganese iron phosphate of the primary particles in the second positive electrode active material is 100 to 400nm. Exemplarily, the average particle size of the lithium manganese iron phosphate of the primary particles of the second positive electrode active material is a range value of one or any two of 100nm, 150nm, 200nm, 300nm, and 400nm. When the primary particles in the second positive electrode active material are maintained within the above range, the particle size of the primary particles of the second positive electrode active material is small, which is conducive to shortening the lithium ion diffusion distance and improving the kinetic properties of the positive electrode active material. It can be matched with the first active material to achieve a large and small particle grading, and achieve the effect of improving the particle packing density, thereby further improving the energy density, low temperature performance and cycle performance of the secondary battery.

[0067] In some embodiments, in the positive electrode sheet, the mass percentage of the first positive electrode active material is 1-95%, and the mass percentage of the second positive electrode active material is 1-95%. Exemplarily, the mass percentage of the first positive electrode active material is 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, or any two of the range values, and the mass percentage of the second positive electrode active material is 1%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, or any two of the range values.

[0068] In some embodiments, the positive electrode plate further includes a conductive agent and a binder.

[0069] In some embodiments, the secondary battery further includes a negative electrode plate, a separator, and an electrolyte.

[0070] In some embodiments, the negative electrode plate includes a negative electrode active material, and the negative electrode active material includes natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, LiSn alloy, LiSnO alloy, Sn, SnO, SnO2, spinel structured lithium titanate Li4Ti5O 12 , at least one of LiAl alloy and metallic lithium.

[0071] In some embodiments, the diaphragm includes a resin or glass fiber in a porous sheet or non-woven fabric form, and the resin includes at least one of polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyethersulfone.

[0072] In a second aspect of the present application, the present application also provides an electrical device comprising the secondary battery.

[0073] The present application is further described below with specific embodiments:

[0074] Example 1

[0075] A secondary battery, wherein the preparation method of the secondary battery comprises the following steps:

[0076] S1. Preparation of positive electrode active materials: There is no special limitation on the preparation method of the first positive electrode active material and the second positive electrode active material in the present application. Specifically, for example, the first positive electrode active material and the second positive electrode active material are synthesized by liquid phase grinding and high-temperature solid phase secondary sintering process. Other conventional methods in the art can also be used to obtain the first positive electrode active material and the second positive electrode active material required for the present application.

[0077] The following takes Example 1 as an example to explain in detail how to prepare the first positive electrode active material and the second positive electrode active material by liquid phase grinding and high temperature solid phase secondary sintering process. The first positive electrode active material and the second positive electrode active material of other examples and comparative examples refer to this preparation method.

[0078] Preparation method of the first positive electrode active material:

[0079] (1) Weigh 6.045 kg FePO4, 4.585 kg Mn3O4, 6.248 kg LiH2PO4, 1.573 kg Li2CO3, 0.026 kg TiO2, 0.047 kg MgO, 0.010 kg CoO, and 0.197 kg glucose respectively; mix the above raw materials evenly, and grind them in a ball mill with deionized water as solvent to a particle size Dv50 of 500 nm;

[0080] (2) spray drying and sintering (490° C., 8 h) to obtain a first sintered product;

[0081] (3) Weigh 0.01 kg WO3 and 0.512 kg glucose respectively, then mix the first sintered product, WO3 and glucose evenly, and grind them for the second time until the particle size Dv50 is 250 nm;

[0082] (4) spray drying and sintering (700°C, 24h) to obtain a second sintered product; the second sintered product is screened and iron removed to obtain a first active material. The chemical expression of the first positive electrode active material is LiMn 0.6 Fe 0.4 PO4.

[0083] D1 and D2 can be adjusted by changing the grinding, spraying and sintering steps in the above preparation process. The relevant information of the first positive electrode active material used in this application is shown in Tables 1 and 2.

[0084] Second positive electrode active material preparation method:

[0085] (1) Weigh 6.045 kg FePO4, 4.585 kg Mn3O4, 6.248 kg LiH2PO4, 1.573 kg Li2CO3, 0.026 kg TiO2, 0.047 kg MgO, 0.010 kg CoO, and 0.197 kg glucose respectively, mix the above raw materials evenly, and grind them in a ball mill with deionized water as solvent to a particle size Dv50 of 800 nm;

[0086] (2) spray drying and sintering (490° C., 8 h) to obtain a first sintered product;

[0087] (3) Weigh 0.01 kg WO3 and 0.512 kg glucose respectively, then mix the first sintered product, WO3 and glucose evenly, and grind them for the second time until the particle size Dv50 is 350 nm;

[0088] (4) spray drying and sintering (725°C, 24h) to obtain a second sintered product. The second sintered product is crushed, sieved and iron removed to obtain a second active material. The chemical expression of the second positive electrode active material is LiMn 0.6 Fe 0.4 PO4.

[0089] Among them, changing the grinding, sintering and crushing steps in the above preparation process can adjust D3. The relevant information of the second positive electrode active material used in this application is detailed in Tables 1-2.

[0090] The first positive electrode active material and the second positive electrode active material are uniformly mixed according to the ratio in Table 2 to obtain a positive electrode active material.

[0091] Because the first positive electrode active material includes a secondary spherical morphology, compared with the preparation method of the first positive electrode active material, there is a crushing process in the second positive electrode active material, so the secondary spherical morphology is destroyed, forming a primary particle morphology of non-secondary spherical morphology. Because the morphology, particle size (Dv10, Dv50, Dv90), and ρ of the two positive electrode active materials are different, and because the positive electrode active material is a mixture of the first positive electrode active material and the second positive electrode active material with different mass percentages, the respective proportions of the first positive electrode active material and the second active material will result in different Dv10, Dv50, Dv90, and ρ of the positive electrode active material.

[0092] S2. The positive electrode active material, the binder PVDF, the conductive carbon black, and the solvent NMP are mixed and stirred evenly to prepare a positive electrode slurry, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil after screening, and then the positive electrode sheet is obtained through baking, rolling, slitting and cutting processes; wherein the weight ratio of the positive electrode active material, the conductive carbon black and the binder PVDF in the positive electrode sheet is 96:2.5:1.5; during the preparation process, the compaction density (P) of the positive electrode sheet is controlled by controlling the rolling pressure and the roller gap, and the single-sided surface density (CW) is changed by controlling the weight of the coated positive electrode slurry, and the specific values ​​are shown in Tables 1 to 2;

[0093] S3. Preparation of negative electrode sheet: negative electrode active material graphite, thickener sodium carboxymethyl cellulose, binder styrene butadiene rubber, conductive agent conductive carbon black are mixed in a mass ratio of 97:1:1:1, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the coated electrode sheet is transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode sheet;

[0094] S4. Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed uniformly to obtain an organic solvent, wherein the volume ratio of EC, EMC and DEC is 20:20:60; then in an argon atmosphere glove box with a water content of <10ppm, the fully dried lithium salt LiPF6 is dissolved in the organic solvent obtained above, mixed uniformly, and an electrolyte is obtained, wherein the concentration of the lithium salt in the electrolyte is 1 mol / L;

[0095] S5. The separator is a commercial non-woven polyolefin resin film;

[0096] S6. The positive electrode sheet, the negative electrode sheet and the commercial separator are rolled up, hot pressed and the tabs are welded. Then, they are placed in an aluminum-plastic film and baked at 85°C for 24 hours. The electrolyte is injected, allowed to stand, formed, and divided into different capacities. The parts are assembled into a secondary battery.

[0097] Examples 2 to 11 and 16

[0098] The secondary batteries in Examples 2 to 11 and 16 are different from those in Example 1 in that the mass percentage of the first positive electrode active material (ω1) and the mass percentage of the second positive electrode active material (ω2) in the positive electrode active material are different, so that Dv in the positive electrode active material is 10 、Dv 50 、Dv 90 , ρ are different, and the compaction density PD of the positive electrode sheet is different by controlling the rolling pressure and the roller gap, as shown in Table 1.

[0099] Embodiments 12 to 13

[0100] The secondary batteries in Examples 12 to 13 are different from those in Example 1 in that the grinding particle sizes in steps (1) and (3) in the preparation method of the first positive electrode active material are changed so that D1 is different and PD in Example 12 is different.

[0101] Embodiments 14 to 15

[0102] The secondary batteries in Examples 14 to 15 are different from those in Example 1 in that the parameters of the spraying process in step (4) in the method for preparing the first positive electrode active material are changed to make D2 different, so that Dv 10 、Dv 50 、Dv 90 different.

[0103] Embodiments 17-18

[0104] The secondary batteries in Examples 17 to 18 differ from those in Example 1 in that c is regulated differently by changing the masses of TiO2, MgO, CoO, and WO3 weighed in steps (1) and (3) in the method for preparing the first positive electrode active material and the second positive electrode active material, and the doping amounts of the same elements in the first positive electrode active material and the second positive electrode active material of each example are the same.

[0105] Embodiments 19 to 20

[0106] The secondary batteries in Examples 19 to 20 differ from those in Example 1 in that the grinding particle sizes in steps (1) and (3) in the preparation method of the second positive electrode active material are changed so that D3 is different and PD of Example 20 is different.

[0107] Examples 21-22

[0108] The secondary batteries in Examples 21 to 22 are different from those in Example 1 in that the PD is different, wherein the PD is controlled by the rolling pressure and the roller gap.

[0109] Embodiments 23-24

[0110] The secondary batteries in Examples 23 to 24 are different from those in Example 1 in that CW is different by changing the weight of the positive electrode slurry applied.

[0111] Embodiment 25

[0112] The secondary battery in Example 25 is different from that in Example 1 in that the mass of FePO4 and Mn3O4 weighed in step (1) of the preparation method of the first positive electrode active material is changed so that the Mn / Fe molar ratio (N1) of the first positive electrode active material is different. The chemical formula of the first positive electrode active material in this example is LiMn 0.5 Fe0.5 PO4.

[0113] Embodiment 26

[0114] The secondary battery in Example 26 is different from that in Example 1 in that the mass of FePO4 and Mn3O4 weighed in step (1) of the preparation method of the second positive electrode active material is changed so that the Mn / Fe molar ratio (N2) of the second positive electrode active material is different. The chemical formula of the second positive electrode active material in this example is LiMn 0.5 Fe 0.5 PO4.

[0115] Embodiment 27

[0116] The difference between this embodiment and embodiment 1 is that in this embodiment, MgO in step (1) of the preparation method of the first positive electrode active material and the second positive electrode active material is replaced by vanadium oxide, and the contents of Mg element and V element are equal.

[0117] Embodiment 28

[0118] The difference between this embodiment and embodiment 1 is that in this embodiment, in the method for preparing the first positive electrode active material and the second positive electrode active material, MgO in step (1) is replaced by niobium oxide, WO3 in step (3) is replaced by indium oxide, and the contents of Mg element and Nb element are equal, and the contents of W element and In element are equal.

[0119] Embodiment 29

[0120] The difference between this embodiment and embodiment 1 is that in the method for preparing the first positive electrode active material and the second positive electrode active material in this embodiment, step (1) does not weigh MgO and CoO, but increases the content of TiO2 so that the increased content of the Ti element is equal to the total content of the Mg element and the Co element.

[0121] Comparative Example 1

[0122] The secondary battery in this comparative example is different from that in Example 1 in that the grinding particle sizes in steps (1) and (3) in the preparation method of the first positive electrode active material are changed so that D1 is different.

[0123] Comparative Example 2

[0124] The secondary battery in this comparative example is different from that in Example 1 in that the grinding particle size in steps (1) and (3) of the preparation method of the first positive electrode active material is changed to make D1, and the rolling pressure and the roller gap are changed to make PD different.

[0125] Comparative Example 3

[0126] The secondary battery in this comparative example is different from that in Example 1 in that the positive electrode active material in this comparative example only contains the second positive electrode active material but does not contain the first positive electrode active material.

[0127] Comparative Example 4

[0128] The secondary battery in this comparative example is different from that in Example 1 in that the positive electrode active material in this comparative example only contains the first positive electrode active material but does not contain the second positive electrode active material.

[0129] The performance test method of secondary batteries is as follows:

[0130] (1) Average particle size (D1) of primary particles of the first positive electrode active material: The positive electrode sheet was cut by argon ion cutting and the cross-section SEM was tested by field emission scanning electron microscopy (SEM). Five secondary spherical particles were randomly selected from the 3K magnification SEM image of the cross-section. The five secondary spherical particles were then magnified to 30K magnification. Ten primary particles with a diameter of 50 nm to 400 nm were randomly selected from the 30K magnification SEM image of each particle. The specific sizes of the primary particles were measured respectively. The sizes of the 50 particles were then averaged to obtain the average particle size D1 of the primary particles of the first positive electrode active material.

[0131] (2) Average particle size (D2) of the secondary particles of the first positive electrode active material: The positive electrode sheet was cut by argon ion cutting and the cross-section was tested by field emission scanning electron microscopy (SEM). Fifteen particles with a diameter of 2 μm to 10 μm were randomly selected from the cross-sectional 3K magnification SEM image and their specific sizes were measured respectively. The sizes of the 15 particles were then averaged to obtain the average particle size of the secondary particles of the first positive electrode active material.

[0132] (3) Referring to GB-T 19077-2016, the particle size of the positive electrode active material was tested by a particle size analysis laser diffractometer to obtain Dv 10 、Dv 50 、Dv 90 .

[0133] (4) True density of positive electrode active material (ρ): refer to the test method of true density in GB / T 24533-2019 and use a true density meter to test the true density of the positive electrode active material.

[0134] (5) Test for the type and content of element M in the positive electrode active material: The positive electrode sheet was cut into small discs with a diameter of 12 mm, and 20 small discs were taken for ICP testing. The type and content of element M were tested by inductively coupled plasma atomic emission spectrometry according to EPA6010D-2018.

[0135] (6) Detection of manganese-iron molar ratio (N1, N2) of the first positive electrode active material and the second positive electrode active material: The first positive electrode active material and the second active material were respectively subjected to ICP testing, and the manganese-iron ratio was tested by inductively coupled plasma atomic emission spectrometry according to EPA 6010D-2018.

[0136] (7) Average particle size of primary particles in the second positive electrode active material (D3): The positive electrode sheet was cut by argon ion cutting and the cross-section SEM was tested by field emission scanning electron microscopy (SEM). Five non-secondary spherical particle areas were randomly selected from the cross-section 3K magnification SEM image. Then, the five areas were enlarged to 30K magnification respectively. Ten primary particles with a diameter of 50 nm to 600 nm were randomly selected from the 30K magnification SEM image. The specific sizes of the primary particles were measured respectively. Then, the average size of the 50 particles was averaged to obtain the average particle size of the primary particles of the second positive electrode active material.

[0137] (8) Test of positive electrode sheet compaction density (PD): The compaction density of the positive electrode sheet is calculated by the formula: PD = 2 × CW ÷ d; where CW is the single-sided surface density of the positive electrode sheet, in units of g / 1540.25 mm 2 ; d is the thickness of the positive electrode active material layer after rolling (the thickness of the positive electrode active material layer is the thickness of the positive electrode sheet minus the thickness of the aluminum foil current collector), in mm, PD in g / cm 3 .

[0138] (9) Test of single-sided density (CW) of positive electrode sheet: 1540.25 mm by weighing method 2 The mass of the positive electrode sheet of the small-area disc is obtained by deducting the weight of the aluminum foil current collector to obtain the mass of the positive electrode active material layer, and then divided by 2 to obtain the mass of the single-sided positive electrode active material layer, the unit is g / 1540.25mm 2 .

[0139] (10) Gram capacity test: At 25°C, the secondary battery was allowed to stand for 10 min, then charged to 4.35 V at a constant current of 1 / 3C and to 0.05C at a constant voltage, then allowed to stand for another 10 min, and then discharged to 2.5 V at a constant current of 1 / 3C. The capacity of the secondary battery was measured and calculated as follows: Gram capacity = capacity (mAh) / mass of active material (g).

[0140] (11) Room temperature DCR test: Fully charge the secondary battery to 4.35 V at 25°C, then discharge at the actual 1C capacity for 30 min and adjust to 50% SOC; then let it stand at 25°C for 30 min, discharge at 5C constant current for 10 s, let it stand for 5 min, and calculate DCR = (voltage before pulse discharge - voltage after pulse discharge) / discharge current.

[0141] (12) -20℃ low temperature capacity retention rate test: Fully charge the secondary battery to 4.35V at 25℃, and record the secondary battery discharge capacity C1 at 25℃; then let it stand at -20℃ for 120min, discharge it to 2.0V at 1C constant current, and record the secondary battery discharge capacity C2; -20℃ capacity retention rate = C2 / C1*100%.

[0142] (13) -20℃ low temperature pulse charging time test: Fully charge the secondary battery to 4.35V at 25℃, then discharge at the actual 1C capacity for 18min, adjust to 70% SOC, stand at -20℃ for 60min, discharge at 0.25C constant current for 10s, stand for 40s, charge at 0.25C constant current to 4.35V or 10s (whichever comes first), stand for 5min, and record the -20℃ low temperature pulse charging time.

[0143] (14) Cycle test of secondary batteries at 45°C: After the secondary batteries are clamped, they are placed in a 45°C constant temperature box for 2 hours, and then cycled at a charge-discharge rate of 1C. That is, the cycle test temperature is 45°C, the voltage range is 2.5V to 4.25V, the discharge depth is 100% DOD, and the charge-discharge rate is 1C. The test is terminated when the capacity retention rate of the lithium-ion battery is ≤80%. Calculate and record the capacity retention rate of the secondary battery after 500 cycles.

[0144] In the following Tables 1 and 2, D1 nm is the average particle size of the primary particles of the first positive electrode active material; D2 μm is the average particle size of the secondary particles of the first positive electrode active material; ρg / cm 3 is the true density of the positive electrode active material; PD g / cm 3 is the compaction density of the positive electrode; Dv 10 μm is the particle size corresponding to the volume cumulative particle size distribution percentage of the positive electrode active material reaching 10%; Dv 50 μm is the particle size corresponding to the volume cumulative particle size distribution percentage of the positive electrode active material reaching 50%; Dv 90 μm is the particle size corresponding to the volume cumulative particle size distribution percentage of the positive electrode active material reaching 90%; c ppm is the content of M element in the positive electrode active material; N1 and N2 are the molar ratios of manganese and iron in the first positive electrode active material and the second positive electrode active material, respectively; Y = D1 × D2 × ρ × PD × (Dv 90 -Dv 10 )÷Dv 50 ÷c, ω1 and ω2 refer to the mass percentage of the first positive electrode active material and the second positive electrode active material in the positive electrode active material, respectively, D3 is the average particle size of the primary particles of the second positive electrode active material, CW is the single-sided surface density of the positive electrode sheet, and R is the membrane resistance of the positive electrode sheet.

[0145] Table 1

[0146]

[0147]

[0148] Table 2

[0149]

[0150]

[0151] The performance test results of the secondary batteries of the above embodiments and comparative examples are shown in Table 3.

[0152] Table 3

[0153]

[0154] It can be seen from the above embodiments and comparative examples that when the positive electrode sheet satisfies the following relationship: 1.85≤D1×D2×ρ×PD×(Dv 90 -Dv 10 )÷Dv 50 When ÷c≤7.42, the secondary battery has higher energy density, lower internal resistance, better low temperature performance (low temperature charging capability, low temperature capacity retention rate) and better cycle performance.

Claims

1. A secondary battery, characterized in that: A positive electrode sheet is included, wherein the positive electrode sheet includes a positive electrode active material, wherein the positive electrode active material includes a first positive electrode active material and a second positive electrode active material, and wherein the positive electrode active material contains an M element; The M element includes at least one of Mg, Ti, V, Zn, Al, Co, W, Mo, Y, Nb, In, La, Zr, Ce, Sr, and Sb; The first positive electrode active material comprises lithium manganese iron phosphate with a secondary spherical morphology, and the lithium manganese iron phosphate with a secondary spherical morphology is formed by aggregation of primary particles; The second positive electrode active material comprises primary particles of lithium manganese iron phosphate; The positive electrode sheet satisfies the following relationship: 1.85≤D1×D2×ρ×PD×(Dv 90 -Dv 10 )÷Dv 50 ÷c≤7.42; Wherein, D1 nm is the average particle size of the primary particles in the lithium manganese iron phosphate with secondary spherical morphology; D2μm is the average particle size of the lithium manganese iron phosphate with secondary spherical morphology; ρg / cm 3 is the true density of the positive electrode active material; PD g / cm 3 is the compaction density of the positive electrode sheet; Dv 10 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 10%; Dv 50 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 50%; Dv 90 μm is the particle size corresponding to when the volume cumulative particle size distribution percentage of the positive electrode active material reaches 90%; c ppm is the content of the M element in the positive electrode active material.

2. The secondary battery according to claim 1, wherein: The D1 nm satisfies: 50 nm ≤ D1 nm ≤ 200 nm.

3. The secondary battery according to claim 1, wherein: The D2μm satisfies: 4.1μm≤D2μm≤9μm.

4. The secondary battery according to claim 1, wherein: The Dv 50 μm satisfies: 0.8μm≤Dv 50 μm≤10.5μm.

5. The secondary battery according to claim 1, wherein: PD g / cm 3 Meets: 2.1g / cm 3 ≤PD g / cm 3 ≤2.55g / cm 3 .

6. The secondary battery according to claim 1, wherein: The positive electrode sheet satisfies at least one of the following: A、4.5μm≤Dv 90 μm≤30μm; B、0.25μm≤Dv 10 μm≤2.6μm; C、3.4g / cm 3 ≤ρg / cm 3 ≤3.6g / cm 3 。 7. The secondary battery according to claim 1, wherein: The single-sided surface density of the positive electrode sheet is 0.125-0.35 g / 1540.25 mm 2 .

8. The secondary battery according to claim 1, wherein: 2000ppm≤c ppm≤8000ppm.

9. The secondary battery according to claim 1, wherein: The average particle size of the lithium manganese iron phosphate primary particles in the second positive electrode active material is 100 to 400 nm.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive electrode active material, positive electrode, battery, and device

    CN118231653A

  • Positive active material, positive pole piece, battery and electric device

    CN118693274A

  • Lithium-ion battery positive electrode plate, and lithium-ion battery and electric device comprising same

    WO2023230985A1

  • Positive electrode active material and preparation method therefor, positive electrode sheet, secondary battery and electric device

    WO2024086978A1

Cited By

  • Lithium manganese iron phosphate positive active material, positive plate, battery, battery pack and electric equipment

    CN120109191A

  • Lithium manganese iron phosphate material as well as preparation method and application thereof

    CN120767326A